The Relationship Between the Anxiety Level of Parents of Children with Special Needs and the Parenting Patterns Provided at Jember State Special Schools - Nadia Lestika Wahyuningtiyas; Mad Zaini; Komarudin (Penerbit Hellow Pustaka, 2025)
Anxiety is an appropriate response to a threat, but anxiety can become abnormal if the level does not match the portion of the threat or comes without any particular reason. This anxiety also occurs in parents who have children with special needs. Having a child with special needs certainly causes feelings of anxiety for parents who care for, educate and raise. This is because children with special needs are handled differently compared to other children who do not have physical or intellectual disabilities. The aim of this research is to determine the relationship between the anxiety level of parents of children with special needs and the parenting style provided at the Jember State Special School. This research uses a quantitative research design with a cross-sectional approach. The population of this research is all parents of children with special needs at the SLB Negeri Jember, with a sample of 111 respondents selected using a purposive sampling technique. The results of research using the Chi-Square statistical test showed that the p value was 0.001 < 0.05 with r = 0.535, which means that the anxiety level of parents of children with special needs has a relationship in the moderate category with the parenting style provided. This indicates that the higher the level of anxiety experienced by parents, the greater the application of permissive parenting. The conclusion from this research is that it is very important for parents to be able to overcome the anxiety they experience, so that it does not affect the parenting style given to their children. It is hoped that this research can become the basis for health and education services to become a good source of information for parents to overcome anxiety and implement correct parenting patterns.